New perspectives on critical marketing and consumer society - Ritch, Elaine L.; McColl, Julie (Emerald Publishing, 2021)
"Digital communication has altered the flow of global information, evolved consumer values and changed consumption practices worldwide. These challenges in the marketplace are being driven by international, social and technological advances. New Perspectives on Critical Marketing and Consumer Society is a groundbreaking textbook allowing readers to understand, critique and engage with this disrupted context. Editors Elaine L. Ritch and Julie McColl bring together a range of specialist contributors to identify and examine widespread social and technological disruptions in the marketplace, covering new topics that illustrate new consumer values, through chapters examining:disruptive innovation, 'woke' branding, data ethics, social shopping, inclusive identities, retail spaces as examples of disruption innovation. The work presents an in-depth discussion of the newest social and technological developments around marketing and consumption across core three themes, 'Disruption and the digital landscape', 'Pseudo Modernity and co-creation of experiences', 'Evolutionary societies and woke branding'. Chapters illustrate how current advances in business and marketing are looking at different approaches for a radically new landscape in marketing and consumer behaviour. New Perspectives on Critical Marketing and Consumer Society provides an illuminating, challenging and thought-provoking guide through changing and fast moving business and retail contexts for all upper-level students of marketing, branding and consumer behaviour--from publisher's website."- Resumé vydavatele
Keywords: spotřebitelské chování; individuální spotřeba; inovace; marketing; consumer behavior; consumption (economics); innovations; elektronické knihy; kolektivní monografie; electronic books; collective monographs